IMPLEMENTASI KEMITRAAN DALAM PEMOLISIAN KOMUNITAS UNTUK PENCEGAHAN PRAKTIK DESTRUCTIVE FISHING (STUDI KASUS PERAIRAN LAUT MALUKU UTARA) - Septiani Kusherawanti (Jurnal Kriminologi Indonesia, 2017)
This study focuses on the issue of partnership implementation on community policingwhich is faced by Directorate Marine Police of Maluku Utara (Ditpolairda Maluku Utara)with community and other agencies in order to prevent destructive fishing. The discussionof this issue is analyzed by social exchange theory and integrated crime prevention. Theauthor uses qualitative approach with descriptive purpose. The result shows that partnershipencounters several problems which are associated with ego sectoral issue and the lack ofpersonels, facilities, and infrastructure. Therefore, every agent possessed in partnershipshould be integrated to form an effective and efficient destructive fishing prevention